Evaluation of the haematology and biochemistry of the silver catfish, Chrysichthys nigrodigitatus as biomarker of environmental pollution in a tropical lagoon - George C. Ugwu; Olufemi O. Soyinka (Syiah Kuala University, 2018)
The objective of the present study was to examine the haematological and biochemical parameters of the silver catfish, Chrysichthys nigrodigitatus, from the Makoko area of a polluted tropical lagoon such as Lagos Lagoon, to serve as a baseline data for the assessment of the health status of the fish and as reference point for future studies. The mean values of the haematological parameters analyzed were: blood haemoglobin, Hb (97.29±4.35g/L); pack cell volume, PCV (29.28±1.23%); red blood cell/total erythrocyte count, RBC (2.97±0.12T/L); white blood cell count, WBC (10.69±0.37g/L); mean cell volume, MCV (95.19±2.28fl); mean corpuscular haemoglobin, MCH (30.53±0.67pg), mean corpuscular haemoglobin concentration, MCHC (33.32±0.38g/dl), and the differential leucocytes. While the mean values of the biochemical parameters were: aspartate transaminase, AST (66.06±6.12 IU/L); alanine transaminase, ALT (12.98±1.10 IU/L), and alkaline phosphatase, ALP (88.01±8.60 IU/L). The findings from this study gave an indication of stress on the health status of the fishes in this lagoon and there is need for proper management strategies to be adopted in monitoring the conditions of the faunal communities in the lagoon. The lagoon indeed showed signs of environmental stress, which eventually pose devastating effect on the health status of the fishes. These have an indirect effect on the coastal communities. There is therefore the need for periodic monitoring and enforcement of environmental laws by respective organisations to ensure health safety of the people especially in the coastal communities.